To simplify the expression 4sin(x) - 5cos(x) + 3sec^2(x), we can start by using the identities:
sin(x) = 1 / csc(x)
cos(x) = 1 / sec(x)
Substituting these identities into the expression, we get:
4(1 / csc(x)) - 5(1 / sec(x)) + 3sec^2(x)
= 4 / csc(x) - 5 / sec(x) + 3sec^2(x)
To further simplify, we can convert the csc(x) and sec(x) terms to sin(x) and cos(x) respectively.
Recall that csc(x) = 1 / sin(x) and sec(x) = 1 / cos(x).
Substituting these identities, we get:
4sin(x) - 5cos(x) + 3(1 / cos^2(x))
= 4sin(x) - 5cos(x) + 3 / cos^2(x)
= 4sin(x) - 5cos(x) + 3sec^2(x)
So the simplified form of the expression 4sin(x) - 5cos(x) + 3sec^2(x) is 4sin(x) - 5cos(x) + 3 / cos^2(x).
4sinx-5cosx+3sec²x
1 answer